Perspektif Fungsi Pengorganisasian Pada Tata Kelola Verifikasi Surat Perjalanan Dinas Pada Organisasi Publik - Asmaraida, Leni; Imania, Katriza (Jurnal PubBis, 2026)
Effective public administrative governance requires a clear, structured, and accountable system of work organization, particularly in the management of state finances. One administrative activity that has direct implications for public financial accountability is official travel undertaken by civil servants. In practice, the verification process of official travel documents still frequently encounters administrative problems, such as incomplete documentation, repeated revisions, and suboptimal work coordination, which in turn lead to delays in administrative completion and budget disbursement. These conditions indicate that issues in the verification of official travel documents are not solely related to regulatory compliance, but are also closely linked to the organizing function within public organizations. This study aims to analyze the governance of official travel document verification from the perspective of the organizing function in public organizations. The research adopts a qualitative approach with a descriptive method. Data sources consist of primary and secondary data obtained through in-depth interviews, observation, and documentation. The study involved eight informants selected purposively based on their roles and involvement in the official travel document verification process. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results show that the governance of official travel document verification has generally been implemented quite well, particularly in terms of work division, work integration, as well as monitoring and reorganization. Nevertheless, obstacles remain in the aspects of task detailing and work coordination, which result in repeated verification processes. These findings highlight the importance of strengthening the organizing function to enhance the effectiveness and administrative orderliness of official travel management